Cold atmospheric plasma : studies on inactivation mechanisms in food-borne pathogens and laboratory strains - Elhenshir, Omar Said Ali (2013)
Food-borne disease remains accountable for high levels of morbidity and mortality in the world. The World Health Organization (WHO) estimated that food-borne and water-borne diarrhoeal diseases kill about 2.2 million people annually (SGM, 2013). In this thesis, studies on microbial inactivation were carried out using Cold Atmospheric plasma (CAP) generated by a radiofrequency (RF) source at RF = 4.6 MHz. The operating gas used was a mixture of helium and oxygen. The study has investigated the effect of CAP on different strains of food-borne bacteria. These included strains/mutants of S. typhimurium, L. monocylogenes and E. coli. The result has shown that CAP has the capability to inactivate a wide range of food-borne bacteria. However, S. typhimurium LT2, E. coli 0157: H7 and E. coli HI 0407 showed more tolerance to CAP treatment than L. monocytogenes strains and E. coli K-12 MG 1655. This result led to further investigations into the role of lipopolysaccharide (LPS) structure in the tolerance to CAP treatment. To investigate the role of LPS structure, derivatives of E. coli K-12 which lack the O-antigen and isogenic mutants of them (core polysaccharide defective) were used. In addition to these strains and mutants, partially and fully restored LPS derivatives of E. coli K-12 MG1655 and S. typhimurium TA98 which is a mutant of S. typhimurium LT2 were also used. No significant differences in the sensitivity to CAP treatments between these mutant and their parental strains were found except between S. typhimurium TA98 and its parental strain. S. typhimurium TA 98 was missing many other genes, therefore it was not comparable to the parental strain. The results suggest no role for the LPS structure regions in the resistance to CAP treatment. The study has also investigated the role of oxidative stress in bacterial inactivation. Mutants of E. coli K-12 BW25113 were a single gene of the OxyR regulated genes has been deleted, were used. Three mutants were found significantly (P < 0.05) more sensitive to CAP treatments than other strains. These mutants were (delta dps), (delta grxA) and (delta sufC). The gene deleted from each mutant is hydrogen peroxide inducible and OxyR regulated (Zheng et al., 2001a). Since each of these genes has an important role in the resistance to oxidative stress, the result suggests the involvement of oxidative stress in inactivation by CAP treatments. To confirm these results and to find out whether the CAP treatment caused DNA damage or mutagenic effects, the Ames strains were used. Exposure to CAP treatment for 5 and 10 seconds caused a significant (P < 0.05) increase in the number of revertant colonies of S. typhimurium TA 100 and S. typhimurium TAI02. The results suggest that CAP caused base-pair substitution in the DNA of S. typhimurium TA 100 (Barnes et al., 1982) and transition/transversion mutations in the DNA of S. typhimurium TA 102 (Levin el al., I 982a) and potentially in the DNA of other bacteria. It can be concluded that CAP inactivates bacteria due to oxidative stress damage and induces mutation in the bacterial DNA. Modification of the Ames strain test was successfully validated. This finding highlights some concerns about application of CAP in dental and wound treatments.